Providing a Constipation Action Plan to Families of Children With Constipation Decreases Health Care Utilization. Issue 5 (18th August 2022) - Hawa, Kathryn; Janse, Sarah; Lee, Jennifer; Bali, Neetu; Vaz, Karla; Yacob, Desale; Di Lorenzo, Carlo; Lu, Peter L.
Abstract : Objectives: To evaluate whether providing a constipation action plan (CAP) to families of children with constipation at outpatient gastroenterology (GI) visits affects health care utilization of the GI department. Methods: We created a CAP to be included in the after visit summary of children seen in our GI Clinic. We compared the number of patient telephone calls, electronic messages, and urgent care (UC) visits, emergency department (ED) visits, and hospitalizations within 3 months after the visit of patients who received the CAP compared to those who did not using inverse probability treatment weighting (IPTW) analysis. For families who received the CAP at a follow-up visit, we compared these variables in the 3 months before and after the CAP was provided using paired t test and McNemar's test as appropriate. Results: We included 336 patients who received the CAP and 2812 who did not. After IPTW adjustment, there were fewer patient telephone calls for patients who received the CAP ( P = 0.0006). The difference in patient electronic messages was not statistically significant ( P = 0.09). For the 45 patients who received the CAP at a follow-up visit, there were on average 1.8 more patient telephone calls made prior to receiving the CAP than after (95% confidence interval (CI) = 0.8–2.8; P = 0.0007) and 2.3 more patient electronic messages received (95% CI = 0.1–4.5; P = 0.04). There were no differences in UC/emergency department visits or hospitalizations. Conclusions: We found that providing a CAP to families of children with constipation decreases health care utilization. Further studies are needed to determine whether this impacts patient outcomes.